Plasma virome and the risk of blood-borne infection in persons with substance use disorder - Abraham J. Kandathil (Nature Portfolio, 2021)
Spread of bloodborne infections, such as HCV and HIV, is a problem, particularly amongst people who inject drugs (PWID). Here, the authors describe and then confirm in observational PWID cohorts that those with more non-pathogenic viruses in plasma were more likely later to acquire HCV than PWID who had fewer of these non-pathogenic viruses.